1997
DOI: 10.1046/j.1365-2036.1997.t01-1-00204.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a single rectal dose of cisapride on delayed gastric emptying

Abstract: Background: Cisapride has an established prokinetic effect in patients with delayed gastric emptying. However, rectal administration of the drug might be preferred in patients with either dysphagia or nausea due to gastroparesis. Aim: To determine the effect of a single rectal dose of cisapride 60 mg on gastric emptying in patients with delayed gastric emptying. Methods: Thirty‐two patients (16 males, 16 females) with demonstrated delayed gastric emptying received a single dose of two suppositories containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…The results of the present study have demonstrated that cisapride was more effective than placebo for the treatment of overall dyspeptic symptoms and of postprandial bloating and discomfort in patients with abnormal baseline electrogastrograms. This response to cisapride may be related to improvement in gastric emptying, as reported in other studies 28 –31 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of the present study have demonstrated that cisapride was more effective than placebo for the treatment of overall dyspeptic symptoms and of postprandial bloating and discomfort in patients with abnormal baseline electrogastrograms. This response to cisapride may be related to improvement in gastric emptying, as reported in other studies 28 –31 …”
Section: Discussionsupporting
confidence: 74%
“…was more effective than 10 mg t.d.s., and that 4 weeks of treatment may be necessary for a complete normalization of gastric myoelectrical activity. Improvement of gastric slow wave rhythmicity with cisapride in patients with gastroparesis has also been reported in a number of previous studies 15 –31 …”
Section: Discussionsupporting
confidence: 67%
“…This open study also suggests that symptomatic improvement is most likely in NUD patients with an abnormal EGG. Trials of treatment in NUD have usually been symptom based, although there are trials where gastric function has been incorporated in the study design 27 –35 . Conventional classification of NUD subdivides the disorder into three groups according to symptoms (ulcer‐like, dysmotility‐like, reflux‐like).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] The effects of rectally administered cisapride were evaluated in patients with scintigraphy-documented delayed gastric emptying due to either diabetes mellitus (4 patients) or functional disorders of gastrointestinal tract motility (24 patients). 13 Two cisapride 30-mg suppositories or two placebo suppositories were administered in a double-blind, randomized, crossover fashion. Three hours after insertion of the suppositories, a radiolabeled test meal, combined liquid and solid phase, was ingested by the subjects, and gastric emptying was evaluated by scintigraphy.…”
Section: Is Rectally Administered Cisapride An Effective Prokinetic Agent?mentioning
confidence: 99%